2016
DOI: 10.1002/jsfa.8097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different agricultural wastes for the production of fruiting bodies and bioactive compounds by medicinal mushroom Cordyceps militaris

Abstract: CS and CCP are effective substrates for the production of fruit bodies and bioactive compounds by C. militaris. This study provides a new approach to decreasing the cost of C. militaris cultivation and dealing with these agricultural wastes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Dong et al [ 41 ] reported that environmental conditions affected the accumulation of active components and the biological efficiency of Cordyceps militaris . Lin et al [ 42 ] showed that the substrate not only affects the yield of C . militaris , but also the production of medicinally active components.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [ 41 ] reported that environmental conditions affected the accumulation of active components and the biological efficiency of Cordyceps militaris . Lin et al [ 42 ] showed that the substrate not only affects the yield of C . militaris , but also the production of medicinally active components.…”
Section: Discussionmentioning
confidence: 99%
“…The poor utilization of these SS has made them a serious environmental problem and increased recovery cost of these materials for the industry. Fortunately, latest researches have recommended the potential use of these SS in animal feeding, recycling substrate and natural active constituents extraction (Doan, Hoseinifar, Tapingkae, Chitmanat, & Mekchay, 2017;Lin et al, 2017; Van, Hoseinifar, Mao, Chitmanat, & Tayyamath, 2017;Wu, Chen, Chang, & Shih, 2013). Thanks to the advantage of the SS in number of applications, compared with CM fruit body, there is a great potential attraction for scientific study and commercial value of SS.…”
mentioning
confidence: 99%
“…However, it is not enough to meet demand for cordycepin. Thus, researches to increase the natural cordycepin content in C. militaris have been peformed through various methods such as breeding by mating or genetic manipulation and C. militaris with higher production of cordycepin is very valuable in the health food or medicine industry [ 9 10 ].…”
mentioning
confidence: 99%